Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1998)
Table of Content One Flight Up – Alex Katz by Vincent Katz What’s Wrong with Culture – Stephan von Huene by Horst Bredekamp Roni Horn Still by Collier Schorr A Unique Vision of Iceland by Styrmir Gunnarsson Standing on the Circumference of Roni Horn’s Asphere by Jerry Gorovoy Notes from an Architect by Diane Lewis Untitled (Flannery) – A Condensation of Acts by Nancy Spector Mariko Mori Cute Futures. Mariko Mori’s Techno-Enlightenment by Norman Bryson No Angels Here, Yet She Lives by Shin’ichi Nakazawa Mariko Mori’s Cyborg Surrealism by Thyrza Nichols Goodeve Beat Streuli Mapping the Anonymous by José Lebrero Stals Beat Streuli’s Gesamtkunstwerk by Arthur C. Danto The Doubleness of Character or the Doubleness of Photography by Taro Amano Everyday Arcadias by Trevor Smith Matthew Ritchie, Insert Motion Capture: Shirin Neshat’s Turbulent by Paul D. Miller Truth and Responsibility, A Conversation with William Kentridge, Les Infos du Paradis by Okwui Enwezor Inside the XXIV Bienal’s Body, Cumulus from America by Valéria Piccoli Spatial Facsimiles and Ambient Spaces, Some Reflections on Site Specificity in Contemporary Art, Cumulus from Europe by Maria Lind
Dreams of the future? “Subjects under advanced capitalism may still wake up and discover in the mirror a creature of skin and bone; yet the moment they step out into the metropolitan field, they at once become a vector of flows and energies, of bodies, information and goods, as a commuter, as a worker, as a consumer.” Yet, having said this, Norman Bryson sees Mariko Mori’s works as visions so agile and spiritualized, that they mutate into angels or bodhisattvas. Roni Horn reflects on “the rolling past and sometimes what’s to come” in her studies of an island far removed from global urbanity: Iceland. The artist is particularly drawn to the unobstructed view that “lays out the planet with an expansiveness and transparence that exists in few other places”. Her pictures of this place, marked by the weather, an extreme climate, and a still recent geological history, transform time and make it permeable to our gaze. It seems that the fragility of existence is more palpable here. The effect is sobering; it sharpens our view of the future and heightens the potential of dreams. Also in this issue an Insert by Matthew Ritchie. (editorial by publisher)
boek
Keywords: Horn, Roni; Streuli, Beat; Mori, Mariko